The Electrofagot Project. New perspectives on bassoon, music, and education - Zúñiga Chanto, Fernando (2025)
Since 2019, my students and I have worked together as a group we have named the Electrofagot Ensemble. The primary objective of the ensemble and the broader Electrofagot Project is to explore how the bassoon can be combined with electronic resources, and to use what we learn to then create new works for individual and multiple players. Working in an ensemble environment to learn new skills and technologies and to then use them to create new exercises and compositions has fostered creative skills far beyond what is generally required when simply interpreting music for bassoon ensemble. For us, it has clearly demonstrated the educational power of working together to create music of our own. This article reviews some of the history of bassoons paired with electronic elements, describes the founding and work of the Electrofagot Ensemble, and notes the benefits of exploring this type of music making together.